Effect of Final Tempering Temperature Variations on the Physical Characteristics (Hardness and Gloss) of Dark Couverture and Milk Couverture - Hanun Kiyasah Izzah; Priskila Mutiara Vina Asnawi; Abiyyu Syafiar; Andryansyah Maulana Mikha Zizou; Azita Laeticea Elfarizan; Renhart Mauritz Hutauruk; Efrina; Leila Siti Chairan (Asosiasi Dosen Muda Indonesia, 2026)
This study aimed to analyze the effect of final tempering temperature variations on the physical characteristics of dark couverture and milk couverture, particularly hardness and gloss. The study used a qualitative experimental approach based on visual and tactile observations, field notes, and photographic documentation. Dark and milk couverture samples were treated at final tempering temperatures of 28°C, 30°C, and 32°C, then molded and evaluated using observation rubrics. The data were analyzed through data preparation, data reduction, coding, theme grouping, data display, preliminary conclusion drawing, and verification. The findings indicate that final tempering temperature affected hardness and gloss in both types of couverture. Dark couverture showed its highest visual gloss at 28°C, a balanced hardness-gloss response at 30°C, and the strongest mechanical resistance at 32°C. Milk couverture showed the highest hardness at 28°C, a balanced response at 30°C, and the highest gloss but lower hardness at 32°C. These findings confirm that dark and milk couverture respond differently to final tempering temperature because of differences in cocoa butter, cocoa solids, sugar, and milk components. This study provides an observation-based framework for chocolate tempering evaluation in culinary laboratories and small-scale confectionery practices.